دراسة تأثير خواص زجاج المباني على استهلاك الطاقة في أنظمة التدفئة والتكييف - عمران عدنان (Latakia University Journal -Engineering Sciences Series, 2019)
يعدّ ترشيد استهلاك الطاقة في الوقت الحاضر من المهام الرئيسية المطروحة ، إذ مع تزايد النشاط البشري في كافة المجالات تتناقص مصادر الطاقة التقليدية بسبب زيادة الطلب عليها . لهذا فإن البحث في مجال تقليل استهلاك الطاقة المصروفة على التدفئة للمباني في الظروف الباردة وعلى التكييف الصيفي في الظروف الحارة يعدّ من المواضيع التي تحظى بأهمية خاصة من أجل زيادة فعالية استخدام الطاقة ، إذ ندرس في هذا البحث تأثير استخدام أنواع مختلفة من الزجاج في واجهات المباني على الأحمال الحرارية للتدفئة والتكييف وبالتالي على الطاقة المستهلكة من أجل تأمين الإضاءة والراحة اللازمة للأشخاص المتواجدين في شتى أنواع المباني المختلفة . Nowadays, the energy consumption reduction is considered as one of the presented basic tasks. However, the classical energy sources are decreasing with the increasing of human activities in all directions because of the increased needs of them. So the search in energy consumption reduction range, which is used for heating the buildings in winter weather and cooling in summer weather, is considered one of the important subjects which pay special attention to energy consumption efficiency increasing. In this research we study the effect of using different kinds of glass in buildings frontages on heating loads for heating and cooling and so on the consumed energy to provide the necessary lighting and comfort for people in all kinds of building.